Ação coletiva passiva - Marangoni, Cíntia (2011)
This research highlights the importance of “passive collective action” in collective lawsuit, in both Brazilian and foreign law in order to enlarge the possibilities of resolution of conflict of interests. This kind of class action is not expressly provided by the Brazilian legal system, which is why many scholars do not acknowledge it in the “system of public civil action”. But scholars who advocate the creation of this institute point out that respecting the “constitutional right of access to justice” and the “principle of non-refoulement” would base its acceptance. The doctrine and jurisprudence are also mentioned as possible reasons for the existence of “passive collective actions”, considering they are seen as “sources of law” (indirect or mediated) by some authors. This is because many scholars have affirmed the possibility of exercising this kind of public civil action, and in the Brazilian court several examples are found, even without being named as “passive collective action”. This work also brings the projects of “collective action codes” created by renowned scholars, and cites the “defendant class actions” of American law, in order to base the defense of these demands. In this study of solutions to the problem of lack of foresight of the “extraordinary passive legitimacy”, it is possible to note that some authors, even not accepting the existence of “passive collective actions”, admit some exceptions, in which a community is placed in the passive side of the collective lawsuit, on the ground to ensure access to jurisdiction. So, trying to meet current needs, considering that the law must evolve with society, we point out the necessity for enactment of laws to regulate this institute. In conclusion, we emphasize the importance of “passive collective actions” in resolving disputes under the collective lawsuit, we highlight the possibility of its exercise by various foundations, and propose to reform the “system of public civil action” in order to include them as one of its kind